Professional and career issues in administrative medicine - Arthur Lazarus (Dove Medical Press, 2009)
Arthur LazarusSenior Director, Global Clinical Development, AstraZeneca Pharmaceuticals, Wilmington, DE, USAAbstract: Administrative medicine is not recognized as a medical specialty in the United States, but increasingly, management-trained physicians are being recruited to fill important roles in hospitals and the life sciences industry. While the opportunities may be substantial, physicians who are interested in pursuing an administrative career should be aware of the challenges embodied in the role of physician executive, such as job turnover, alienation from peers, and overcoming the “caducean ceiling.” Healthcare systems that are serious about transforming themselves must harness the energies of physicians as organizational leaders, and physicians who are equal to the task must supplement their medical training with training in business and management.Keywords: healthcare administration, medical management, physician executive, leadership